2014
DOI: 10.1007/s00167-014-3050-1
|View full text |Cite|
|
Sign up to set email alerts
|

Brake response time returns to the pre-surgical level 6 weeks after unicompartmental knee arthroplasty

Abstract: On the basis of the current findings, it is concluded that brake response time returns to pre-operative levels 6 weeks after UKA surgery. Therefore, it is proposed that driving be abstained from for that period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…A similar correlation was found in these patients between stepping and standing tests and brake response time [22]. Patients with a right TKA had normal brake response times and total brake times 2 to 8 weeks postoperatively [9,28,36,37,42,50,57] and normal brake response times 0 to 3 weeks after a left TKA [36,37,41,50,57]. Data showed that a step test was the best predictor of safety when correlated with total brake time after TKA [28].…”
Section: Observer-reported Outcome Measuressupporting
confidence: 64%
“…A similar correlation was found in these patients between stepping and standing tests and brake response time [22]. Patients with a right TKA had normal brake response times and total brake times 2 to 8 weeks postoperatively [9,28,36,37,42,50,57] and normal brake response times 0 to 3 weeks after a left TKA [36,37,41,50,57]. Data showed that a step test was the best predictor of safety when correlated with total brake time after TKA [28].…”
Section: Observer-reported Outcome Measuressupporting
confidence: 64%
“…The overall quality of the studies varied and ranged from 3 points (poor quality) [41] to 10 points (good quality) [35], with four studies reaching a 9 point score (good quality) [36][37][38][39] (Table 1). The ten studies comprised a sample of 309 patients who underwent TKA (197 right TKA, 99 left TKA, and 13 bilateral TKA) and whose BRT was measured preoperatively and at different points in time after surgery (Appendix B) in eight different car simulators.…”
Section: Quality Assessment Of the Included Studiesmentioning
confidence: 99%
“…The overall quality of the studies varied and ranged from 3 points (poor quality) [41] to 10 points (good quality) [35], with four studies reaching a 9 point score (good quality) [36][37][38][39] (Table 1).…”
Section: Quality Assessment Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations